Fixed Point in Topological Vector Space-Valued Cone Metric Spaces. (14th June 2010) - Azam, Akbar; Beg, Ismat; Arshad, Muhammad
Abstract : We obtain common fixed points of a pair of mappings satisfying a generalized contractive type condition in TVS-valued cone metric spaces. Our results generalize some well-known recent results in the literature.